KONSTRUKSI WACANA DAN PENCITRAAN DALAM DEBAT PERDANA CALON GUBERNUR DAN WAKIL GUBERNUR DKI - Yusup Irawan (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
By analyzing a political debate, we can uncover a lot of political things implied. Thiscritical discourse analysis research with the framework of Hamad’s (2007) andFairclough’s (1995) theory analized the first political debate among the candidatepairs of governor and vice governor of Jakarta 2017. Specifically, the research is aimedat (1) describing discourse construction built by each candidate pair, (2) uncoveringself-image of each pair, and (3) uncovering the negatif image created by each candidateto attack the other candidates. This descriptive-qualitative research found that firstthere are a lot of positive issues raised by incumbents. On the other side, theoppositions tended to raised negative issues which potentially to drop the incumbents’image. The second, the incumbents tended to build his image as a successful leaders towelfare people. Conversely, the oppositions tended to build their images as theprospective leaders which pro to people, contracondemnation, and respect to ethic andmorality. Related to the image of political opponents, this research found that theincumbents as well as the oppositions constructed a various of negative imaging toattack their political opponents.